Study the Gene Expression of PIK3CA in Tissue and Blood Samples of Iraqi Patients with Colorectal Cancer - Azeez, Rasha Abbas; Al-Jowari, Suha Abdul-Khaliq; Mahmood, Hayder Jamal (Journal of Contemporary Medical Sciences, 2023)
Objective: The primary objective of this investigation is to explore the correlation between gene expression of PIKCA3 and colorectal cancer in both tissue and blood samples, while also performing a comparative analysis between these sample types. Methods: This research involved the collection of blood and tissue samples. The study was conducted at the Gastroenterology Hospital within the Medical City Department in Baghdad, Iraq, spanning from December 2021 to December 2022. A total of 80 volunteers, encompassing both genders and aged between 24 and 77, participated in the study. The Real Time qRT-PCR analysis method was employed to assess the expression of PIKCA3 genes within patient and control groups. Results: The findings indicate significant distinctions in Ct PIK3CA between blood and tissue samples across all study groups. Moreover, PIK3CA expression displayed a notable association with CRC patients, showing higher expression levels compared to the other groups. This disparity was particularly pronounced when comparing tissue and blood samples. Statistical analysis, specifically Receiver Operating Characteristic (ROC) Curve Analysis, affirmed the excellent predictive capacity of the AUC (Area Under the Curve) value. The study established that PIK3CA gene expression in tissue outperformed that in blood, demonstrating a considerably elevated gene expression in tissue (p<0.001). Notably, the fold increase in gene expression within CRC patients was significantly higher compared to the group of healthy participants, with values of 23.630 in blood samples and 124.810 in tissue samples, respectively. The present study underscores the prevalence of PIK3CA gene mutations in colorectal carcinomas. Conclusion: The frequent occurrence of PIK3CA gene mutations in colorectal carcinomas may hold promise for the development of targeted therapy combinations. These could involve inhibiting both the PI3K kinase itself and addressing associated pathway anomalies.